HUBUNGAN ANTARA BIG FIVE PERSONALITY TRAIT DENGAN CELEBRITY WORSHIP PADA PENGGEMAR K-POP DI MANADO DAN MINAHASA - Pakasi, Natalia C. M.; Mandang, Jofie H.; Hartati, Meike E. (PSIKOPEDIA, 2024)
The aim of this research is to analyze the relationship between each personality in the big five personality traits and celebrity worship among K-Pop fans in Manado and Minahasa and to simultaneously analyze the big five personality trait variables with celebrity worship among K-Pop fans in Manado and Minahasa. This research used quantitative research methods with a sample of 97 early adult subjects with an age range of 18-40 years. Based on the results of this research, it can be concluded that there is a simultaneous relationship between the big five personality traits and celebrity worship among K-Pop fans in Manado and Minahasa with the Sig value. F change = 0.000 < 0.05, with a correlation coefficient of 0.720. Based on the results of the partial correlation test, each big five personality trait has a relationship with celebrity worship with the same sig value, namely 0.000 < 0.05, while the results for the level of relationship have different results. The big five traits with the highest correlation to celebrity worship are neuroticism with a Pearson correlation value of 0.832, next is conscientiousness with a Pearson correlation value of 0.815, agreeableness with a Pearson correlation value of 0.749, openness to experience with a Pearson correlation value of 0.716 and the lowest is extraversion with a Pearson correlation value. 0.51